2004
DOI: 10.1353/asi.2004.0005
|View full text |Cite
|
Sign up to set email alerts
|

Hunter-Gatherers and the Archaeology of Discard Behavior: An Analysis of Surface Stone Artifacts from Sturt National Park, Western New South Wales, Australia

Abstract: An analysis of surface scatters of stone artifacts from late Holocene contexts at Stud Creek, Sturt National Park in the northwest of New South Wales, Australia, is reported. A sedimentological and archaeological chronology for Stud Creek shows archaeological remains are no older than 2000 years and Stud Creek saw repeated occupation during the last two millennia. Methods are proposed whereby conflated stone artifact assemblages from different locations within the Stud Creek catchment can be analyzed to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 42 publications
0
45
0
3
Order By: Relevance
“…For the past ten years, the Western New South Wales Archaeology Program (WNSWAP) has been developing not only new ways of recording and analysing this extensive surface (i.e., open site) record ( [5], [9], [10], [11], [12], [13], [14], [15], [16]), but also a chronology of occupation based on radiocarbon dating of charcoal from the hearths and Optically Stimulated Luminescence (OSL) dating of the surfaces on which the archaeological record now rests ( [17], [18], [19]). As indicated in Figure 1, we have studied these surface artefact assemblages from a number of locations across a large area of western NSW.…”
Section: Location and Description Of The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…For the past ten years, the Western New South Wales Archaeology Program (WNSWAP) has been developing not only new ways of recording and analysing this extensive surface (i.e., open site) record ( [5], [9], [10], [11], [12], [13], [14], [15], [16]), but also a chronology of occupation based on radiocarbon dating of charcoal from the hearths and Optically Stimulated Luminescence (OSL) dating of the surfaces on which the archaeological record now rests ( [17], [18], [19]). As indicated in Figure 1, we have studied these surface artefact assemblages from a number of locations across a large area of western NSW.…”
Section: Location and Description Of The Study Areamentioning
confidence: 99%
“…Attributes included those recorded during previous surveys in western NSW ( [15], [16]) following definitions in Holdaway and Stern ([21]). These included identification of raw materials, attributes related to the way flakes were removed from the core, tool forms, clast size and technologically orientated sizes.…”
mentioning
confidence: 99%
“…Where the contemporary creek lines are cut into alluvial sedimentary sequences, unconformities are observed that represent either substantial hiatuses in valley floor aggradation or, more likely, periods dominated by valley floor erosion. For example, the sequence recorded at Stud Creek contained gaps of several thousand years in the depositional record of the Holocene (Fanning & Holdaway, 2001b;Holdaway, Shiner, & Fanning, 2004). The absence of buried paleosols in this sequence suggests that the unconformities represent more than just the product of stable periods in the evolution of the landscape, when aggradation temporarily ceased.…”
Section: The Geomorphic Contextmentioning
confidence: 98%
“…Surface exposure means that substantial numbers of artifacts can be analyzed very economically, leading to new insights on the nature of assemblage composition (e.g., Holdaway, Shiner, & Fanning, 2004;Douglass et al, 2008). However, failure to understand the nature of erosion and aggradation, and the episodic nature of events that shape surface sediments including the archaeological record, can lead to quite erroneous conclusions .…”
Section: Accounting For the Presence And Absence Of Surface Artifactsmentioning
confidence: 99%
See 1 more Smart Citation